Computational fluid dynamics of flapping wings - Ng, Eric Tee-Sang. (2013)
This paper studies the Computational Fluid Dynamics of flapping wings using the JET Code, which uses the large eddy simulation model and the immersed boundary method. The objective of this study was to investigate the effects of various parameters of pitching and plunging motion in the generation of the lift and drag coefficients. In doing so, the JET Code was further validated, and an optimal phase lag of an oscillating pitching motion behind that of plunging was found. This was a phase lag of 110° that resulted in maximum thrust generation, corresponding to a pitching amplitude of 20° about a 0° angle of attack, plunging amplitude of 0.9 of the chord length, oscillating frequency of 100°/s and Reynolds number of 1000.